Comparative Evaluation of Quantitative Protein Measurement of 12-Hour and 24-hour Urine Sample for the Diagnosis of Nephrotic Syndrome and their Correlation with Spot Urinary Protein Creatinine Ratio (Sir Salimullah Medical College Journal, 2022)
Background: The amount of protein excretion is a reflection of disease activity in Nephrotic Syndrome. 24-hour urine collection has remained as the method of choice to quantify proteinuria. An alternative method for quantitative evaluation of proteinuria is measuring the ratio of protein or albumin to creatinine in an untimed ‘‘spot’’ urine specimen.Objective: To compare 12-hour versus 24-hour proteinuria in nephrotic syndrome and its correlation to spot urinary protein creatinine ratio.Materials & Methods: A comparative cross-sectional study was conducted in the Department of Pediatrics, Sir Salimullah Medical College Mitford Hospital (SSMC & MH), Dhaka over a period from September 2016 to June 2017. All the babies developing 1st attack of Nephrotic Syndrome and meeting the clinical criteria were included in the study. Complete history was taken from accompanying attendants. Thorough clinical examinations and relevant laboratory investigations (12- hour day urinary protein, 12-hour night urinary protein, 24-hour urinary total protein, S. Albumin, S. Cholesterol, Urinary spot Protein Creatinine ratio) were done. All the information was recorded in the fixed protocol. Collected data were classified, edited, coded and entered into computer for statistical analyses.Results: Out of 50 cases, the mean age was found 58.3±29.0 months. 12-hour day urinary protein was found 2.02±0.167 gm/m2/12 hours, mean; 12-hour night urinary protein was found 2.12±2.18 gm/m2/12 hours, mean; 24-hour urinary total protein was found 4.10±3.32 gm/m2/24 hours. The mean spot urinary protein creatinine ratio was found 12.58±7.21 with range from 2.02 to 29.85. There was no statistically significant difference between 12- hour day sample and 12-hour night sample. There was also no significant difference between 12-hour day & night sample with 24-hour sample. Results of all 03 samples were comparable to urinary protein creatinine ratio.Conclusion: This study reveals no statistically significant difference in quantitative estimation of 12-hour day and night protein with 24-hour urinary total protein. The 12- hour day and night protein and urinary total protein were comparable with each other and also with urinary spot protein creatinine ratio.So 12-hour day or night urinary total protein may be a diagnostic tool for nephrotic syndrome.Sir Salimullah Med Coll J 2021; 29(2): 105-111